(untitled) (Research, Society and Development, 2021)
This article has a descriptive character, aiming to analyze the potential of the insertion of astronomy in Physics Teaching, involving the application of knowledge about matter and energy in a phenomenological perspective through the theory of planetary formation. A bibliographical research based on books, articles, monographs, dissertations, theses and documents that guide the construction of the curriculum of Nature Sciences in High School was developed, allowing a contextualized approach in the process of teaching and learning in Physics. The specific competencies of the area of Natural Sciences and its Technologies present in the Common National Curricular Base (BNCC) encourage the practice of scientific research and highlight the importance of this approach in the contemporary world. Moreover, Science enables the observation, experimentation and investigation of phenomena present in everyday life, which involve astronomy, arousing interest and curiosity in students, bringing contemporary aspects in the teaching of classical mechanics. Considering that astronomy has a motivating potential for students and teachers, its approach is important in understanding concepts, promoting substantial discussions, consenting in the process of scientific literacy in basic education.